Analisis Pengaruh Penerapan Strategi Bauran Pemasaran terhadap Keputusan Pembelian pada UMKM Serba Nanas Alam Sari Subang Jawa Barat - Rosmawati, Kania; Azzahra, Fatimah; Fikri, Muhammad Rom Ali (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
UMKM One of the producers in Subang offering processed pineapples is Serba Nanas Alam Sari. Processed pineapple sales are erratic. Businesses must create a strong marketing mix strategy in order to overcome consumer preferences and market rivalry. The purpose of this study is to examine how purchase decisions at Serba Nanas Alam Sari UMKM in Subang, West Java, are affected by the application of a marketing mix approach. In order to collect data for this study, 100 UMKM customers were given questionnaires. Mixed methods were used in this research. The techniques employed for gathering data included surveys, interviews, documentation, and observation. A Likert scale is used for variable measurement, and MSI is used to alter it. Multiple linear regression data analysis was used to ascertain the impact of place, promotion, price, and product variables on consumer purchase decisions. The study's findings indicate that the significant value is less than 0.05, indicating that purchase decisions are influenced by product, price, place, and promotion all at the same time. With a result of 1,042, the product variable has the biggest impact. This is due to the product's variety, good taste, and guaranteed product quality. The variables that affect promotion, pricing, and location are next in line. Based on the study's findings, Serba Nanas Alam Sari UMKM can benefit from an efficient marketing plan that combines quality products, competitive pricing, effective distribution, and eye-catching promotions to influence more customers' purchases.